Studi Penerapan Online Learning di PT. Krakatau Steel Tbk. - Pramono, Abdul Chatim; Neng Eti Setiawati, Neng Eti Setiawati; Perdana, Fachrudin (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2022)
The purpose of this study is to describe the application of Online Learning at PT. Krakatau Steel, Tbk and to find out what factors influence the level of employee competence to be maintained. Employee education and training is a means of developing human resources. Even during the Covid-19 pandemic, the company continues to provide education and training. One of the efforts to increase employee competence during this pandemic is the application of online learning. Using qualitative research methods with a phenomenological descriptive approach. As research samples or sources of information are instructors, organizers and training participants. Data collection techniques using interviews and observation. The research subjects are employees of PT. Krakatau Steel, Tbk. The object of research is an Online Learning application through an application called KrasDemy. The results showed that training with the implementation of KrasDemy online learning greatly facilitated the employees (participants) because it was flexible anywhere and anytime. The factor that affects the application of online learning is the Covid-19 pandemic, so you must maintain physical distance with face-to-face training (offline) to minimize the spread of Covid-19. Meanwhile, it must continue to be carried out, so that online training with KrasDemy is carried out.